2011
DOI: 10.1364/oe.19.012342
|View full text |Cite
|
Sign up to set email alerts
|

Superfocusing of electric or magnetic fields using conical metal tips: effect of mode symmetry on the plasmon excitation method

Abstract: We compare single- and double-sided excitation methods of adiabatic surface plasmon polariton (SPP) wave superfocusing for scattering-type metallic near-field scanning optical microscopy (s-NSOM). Using the results of full 3D finite difference time domain analyses, the differences in field enhancement factors are explained and reveal the mode selectivity of a conical NSOM tip for adiabatic SPP superfocusing. Exploiting the mode-symmetric nature of the tip further, we also show that it is possible to selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This bandwidth may in principle be further enhanced by using more sophisticated grating designs such as fan gratings [111]. The coupling efficiency of the grating can be tailored by using non-rectangular slit shapes or chirped gratings [81] or by adapting the wavefront of the laser radiation that is incident on the grating [85].…”
Section: Fabrication Of Conical Gold Tapers and Grating Coupling To Pmentioning
confidence: 99%
See 2 more Smart Citations
“…This bandwidth may in principle be further enhanced by using more sophisticated grating designs such as fan gratings [111]. The coupling efficiency of the grating can be tailored by using non-rectangular slit shapes or chirped gratings [81] or by adapting the wavefront of the laser radiation that is incident on the grating [85].…”
Section: Fabrication Of Conical Gold Tapers and Grating Coupling To Pmentioning
confidence: 99%
“…In principle, polarization control may be achieved by attaching nanoresonators with defined geometry or by using phase-locked pairs of excitation pulses, as illustrated, e.g. in [81]. Alternatively, conventional, dielectric scanning probe tapers may of course be used to generate optical near fields with arbitrary polarization state.…”
Section: Properties and Potential Of Plasmon Nanofocusingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theoretical studies have shown such a phenomenon [32][33][34][35]. The TM SPP mode can be excited using an axially symmetric grating under radially polarized excitation [36,37] or double-sided E-symmetric excitation [38] or asymmetric excitation via grating coupling on just one side of the tip [39].…”
Section: Nanofocusing In Snom Probes: the Axisymmetric Structurementioning
confidence: 99%
“…Tip on aperture probes and probes based on a monopole antenna can also be included in this category [53,54]. An asymmetric illumination scheme can be used as an alternative to a structural asymmetry [55]: surface plasmons are excited only on one side of an apertureless probe via an opening close to the probe base in the offset aperture probe [56], while asymmetric single-sided SPP excitation results in field localization in an axisymmetric apertureless probe [38].…”
Section: Nanofocusing In Snom Probes: the Asymmetric Structurementioning
confidence: 99%